2020
DOI: 10.1002/ccr3.2912
|View full text |Cite
|
Sign up to set email alerts
|

Herpes zoster in an 11‐month‐old immunocompetent infant: A rare case report

Abstract: Herpes zoster generally occurs after the exposure of VZV following varicella. This case report emphasizes a rare case of HZ in an infant without prior history of varicella or its exposure in the baby, other siblings, and mother during or after the pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…22,23 Childhood HZ is slightly more common in males and generally unilateral single dermatomes can be involved. 24 In this case series also all the cases were male child and a single dermatome was involved. Some studies have demonstrated that the most commonly involved dermatome is thoracic dermatome (50%) followed by lumbar dermatome (23.53%), and the cervical, trigeminal and sacral dermatomes were more frequently involved in younger children, while thoracic or lumbar dermatome was involved in older children.…”
Section: Discussionmentioning
confidence: 62%
“…22,23 Childhood HZ is slightly more common in males and generally unilateral single dermatomes can be involved. 24 In this case series also all the cases were male child and a single dermatome was involved. Some studies have demonstrated that the most commonly involved dermatome is thoracic dermatome (50%) followed by lumbar dermatome (23.53%), and the cervical, trigeminal and sacral dermatomes were more frequently involved in younger children, while thoracic or lumbar dermatome was involved in older children.…”
Section: Discussionmentioning
confidence: 62%